Caracteriza????o filogen??tica e funcional da microbiota do intestino do Cupim Comedor de Serapilheira Syntermes wheeleri (Termitidae: Syntermitinae) - Santana, Renata Henrique (2017)
Termites are well known for their ability to cause agricultural losses and building damage through their ability to digest lignocellulose; however, termites provide important ecosystem services, such as soil bioturbation and nutrient cycling. Microorganisms in the digestive tract of termites are responsible for several of these functions. Syntermes wheeleri (Syntermitinae) is a litter-feeding termite species of the Termitidae family that is abundant in the Brazilian Cerrado. In this work, we characterized the gut microbiota of S. wheeleri, aiming to better understand the ecosystem function of termite-microbe symbiosis and its evolutionary history. First, the gut microbiota composition of worker termites was described by pyrosequencing phylogenetic markers (amplicons), specifically 16S rRNA (archaea and bacteria) and 18S rRNA (fungi). The resulting bacterial taxonomic profile was then compared with the gut microbiota of several other termite species and feeding guilds. To identify the functional groups and activity of the microbiota in the whole gut and the largest proctodeal segments (P1 and P3), the metagenome and metatranscriptome were sequenced by next-generation sequencing (NGS). Amplicon sequences revealed a high abundance of Firmicutes in S. wheeleri, which was not observed in the other termite species. Most archaea belonged to the methanogen orders, and the most abundant fungal classes were Dothideomycetes, Sordariomycetes, and Eurotiomycetes, which have saprophytic species. Ordination analysis of the relative abundance of bacterial taxa showed that the S. wheeleri gut microbiota did not cluster with the microbiota of termites of different clades and feeding guilds. This finding suggests that both variables are important in microbial assembly in termites. The taxonomic profile generated by NGS analysis of the metagenome was similar to the results of amplicon analysis, with higher Firmicutes abundance in P1 and higher Spirochaetes abundance in P3. Additionally, alignment of ribosomal protein S3 identified possible compartment-specific bacterial lineages of Firmicutes, Spirochaetes, Actinobacteria, Bacteroidetes, and Tenericutes. The results of our study revealed a vast metabolic repertoire of termite gut microbes, which supplies nutrients for the host. Differences identified in the P1 and P3 metabolic pathways are likely caused by differences in O2 concentration. As for biomass conversion, the most abundant glycosyl hydrolases (necessary for lignocellulose digestion) detected in the S. wheeleri gut microbiota are a mixture of those that are most abundant in litter-feeding species (fungus growers), as well as wood-, soil-, and dung-feeding species. In addition, putative bacterial laccases (involved in lignin degradation) were detected. Besides the known function of the termite gut microbiota in carbon and nitrogen cycling, we found evidence of its possible involvement in arsenic cycling. This study adds information about microbial establishment in the termite gut, with functional groups selected based on feeding substrate, instead of specific microbial lineages. In addition, our results show that the metagenome can be used to identify molecules with potential industrial applications, such as enzymes useful in biofuel production.